HYPOGLYCEMIC EFFECT OF TINOSPORA CORDIFOLIA IN ALBINO RATS - V. AGLAWE; S. KINKAR; A. EKTARE (The Bioscan, 2011)
The present study is designed to investigate the hypoglycemic effect of Tinospora cordifolia in normal rats of the wistar strain. The rats weighing 180-300g were administered intraperitonealy with the alcoholic leaf extract of Tinospora cordifolia with a single dose of 0.5g/kg body weight from a period of Day 1 to 24 days. It produced significant decrease in the levels of blood glucose.The results showed that the extract of Tinospora cordifolia is antidiabetogenic and possess hypoglycemic effects.